2021
DOI: 10.1038/s41467-021-22614-1
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Characterization of spike glycoprotein of SARS-CoV-2 on virus entry and its immune cross-reactivity with SARS-CoV

Abstract: A Correction to this paper has been published: https://doi.org/10.1038/s41467-021-22614-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The clinical sign of respiratory tract was confirmed in rhesus macaques, golden hamster, domestic cats, tiger, lion, mink, and ferret; Viral transmission was observed in rhesus macaques, golden hamster, domestic cats, lion, tiger, mink, ferret, and Egyptian fruit bat 12–23,25–29,31–33,50 . For cell lines, SARS‐CoV‐2 can infect and replicate in human Caco2, Calu3, NHBE, and lung epithelial line A549 25,51–56 . Meanwhile, SARS‐CoV‐2 can replicate in rhesus monkey LLCMK2, rabbit RK‐13, cat CRFK, and pig ST, and PK‐15 cells lines 25,57 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The clinical sign of respiratory tract was confirmed in rhesus macaques, golden hamster, domestic cats, tiger, lion, mink, and ferret; Viral transmission was observed in rhesus macaques, golden hamster, domestic cats, lion, tiger, mink, ferret, and Egyptian fruit bat 12–23,25–29,31–33,50 . For cell lines, SARS‐CoV‐2 can infect and replicate in human Caco2, Calu3, NHBE, and lung epithelial line A549 25,51–56 . Meanwhile, SARS‐CoV‐2 can replicate in rhesus monkey LLCMK2, rabbit RK‐13, cat CRFK, and pig ST, and PK‐15 cells lines 25,57 .…”
Section: Resultsmentioning
confidence: 94%
“…[12][13][14][15][16][17][18][19][20][21][22][23][25][26][27][28][29][31][32][33]50 For cell lines, SARS-CoV-2 can infect and replicate in human Caco2, Calu3, NHBE, and lung epithelial line A549. 25,[51][52][53][54][55][56] Meanwhile, SARS-CoV-2 can replicate in rhesus monkey LLCMK2, rabbit RK-13, cat CRFK, and pig ST, and PK-15 cells lines. 25,57 Overall, the above reports revealed that the SARS-CoV-2 cell entry, or at the least, the recognition of ACE2 to SARS-CoV-2 has widely existed in livestock and wide animals.…”
Section: Summary Of Animals and Cells Affected By Sars-cov-2mentioning
confidence: 99%
“…ACE2 is the primary receptor for SARS-CoV-2 cellular entry. [34] This receptor is widely expressed across multiple organs, including on epithelial cells of the nasopharynx, heart, lungs, kidney, intestine, central nervous system, and blood vessels. [35] Recent single-cell RNA-sequence (scRNA-seq) analysis revealed ACE2 gene expression in multiple epithelial cell types across the respiratory tract, most notably in nasal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using pseudoviruses enables research of highly pathogenic viruses without the requirement for highly secure biosafety facilities, which has greatly bene ted research on COVID-19 [47][48][49][50]. However, the previously reported SARS-CoV-2-related recombinant virus either simulated the functional structure of S and N protein or incorporated fragments of its nucleic acids, and failed to simulate the functional structure of complete SARS-CoV-2 particles.…”
Section: Introductionmentioning
confidence: 99%